Divine Roominess: Spatial and Music Analogies in Hans Urs von Balthasar and Robert Jenson. Issue 3 (August 2019) - Lett, Jacob
Hans Urs von Balthasar and Robert Jenson both spatialize God by depicting the triune life as "roomy". Theologians have employed spatial analogies readily since the inception of the "trinitarian revival" of the 20th century. In recent days, however, theologians have begun critiquing divine spatial imagery. In particular, the spatialized grammar of Balthasar's trinitarian theology has attracted criticism. In this article, I review Balthasar's divine spatial analogies and show how "bodily" readings of them have provoked criticism. I then repair Balthasar by applying Jenson's musical rendition of "divine roominess" to Balthasar's spatial analogies, suggesting that musical conceptions of space resolve some of the concerns theologians raise with Balthasar's trinitarian theology in particular and spatial analogies in general.